Tổng hợp, đặc trưng và tính chất vật liệu ZnO pha tạp C, Ce - Đại, Lưu Minh; Nhiệm, Đào Ngọc; Việt Hà, Lưu Thị; Hân, Nguyễn Ngọc (Vietnam Journal of Chemistry, 2016)
The materials of Cerium, carbon co-doped Zinc Oxide was prepared at 180 oC by the hydrothermal method. Its products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), UV-VIS-spectroscopy. The XRD spectra show that the samples with percentage of Ce doped less than 2 mol% have single phase and hexagonal wurtzite structures. The SEM images show that the material are hierarchical nanostructure with the nano scales beam into the flowers. The bandgap energy of cerium, carbon co-doped Zinc Oxide is approximate 2.8 eV. The obtained results endicated that the material are a promising photocatalyst activing under visible-light inrradition. Keywords. Cerium, carbon co-doped Zinc Oxide; hydrothermal method.